Penyelenggaraan Operasional Penerimaan, Penyimpanan, dan Pendistribusian Bahan Baku Poultry, Fish, Seafood di PT. XYZ - Azizah Priastuti; Ita Fatkhur R; Any Sutiadiningsih; Asrul Bahar (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to find out: 1) operational implementation of raw material reception for poultry, fish, seafood; 2) organizing operational storage of poultry, fish and seafood raw materials; 3) carrying out operational distribution of poultry, fish and seafood raw materials at PT. XYZ. This research uses a qualitative descriptive research approach. Data collection techniques using interviews and document study. The data analysis technique uses qualitative descriptive analysis. The research results show that the operations for receiving, storing and distributing raw materials for poultry, fish and seafood have been carried out well. The implementation has followed the Standard Operating Procedures (SOP) set by the company. Acceptance is carried out by checking the quality and quantity of raw materials. Storage is carried out in the freezer with a First In First Out (FIFO) system. Then distribution is carried out if there is a request from the production department accompanied by a storeroom requisition.